ANALISIS KESALAHAN SISWA KELAS XI MIA 1 MADRASAH ALIYAH AL-KHAIRAAT KALANGKANGAN DALAM MENYELESAIKAN SOAL CERITA BARISAN DAN DERET ARITMETIKA BERDASARKAN TAHAPAN NEWMAN: Error Analysis Of Students in Class XI MIA 1 of Madrasah Aliyah Al-Khairaat Kalangkangan in Solving Analytical Question of Arithmetic Progression Based on Newman’s Stages - Hapsa; Rochaminah, Sutji; Murdiana, I Nyoman (Universitas Tadulako, 2023)
The purpose of this study was to describe of errors made by student in class XI MIA 1 Madrasah Aliyah Al-khairaat kalangkangan in solving narrative questions on arithmetic sequences and series based on newman’s stages. This type of research is descriptive using a qualitative approach. Subjects were 2 students drawn from 36 class XI MIA 1. The results of this study were (1) no reading error made by the subjects as they able to read out the questions given very well. (2) no of the subjects made a comprehension error, this could be seen during the interview, all research subjects were able to provide known and asked information from the questions. (3) Transformation errors were made by all research subjects. This transformation error is characterized by the subject failing to change the problem into the correct mathematical model and the subject being wrong in determining the formula to be used to solve the problem. (4) Process skill errors were made by all research subjects, this was indicated by the subject knowing the steps to solve the problem but was wrong due to the subject's error at the transformation stage and the subject could not carry out the mathematical calculation process correctly. (5) errors in writing the encoding error were made by all research subjects, this was indicated by the subject not determining the final result of the answer and the subject being wrong in determining the correct answer due to errors made in the previous stage.